(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The author of the article analyses foreign research concerning the problem of using learning strale gies The essence and main features of learning strategies are clarified, and their classification and a model of teaching to use them are presented. The conclusion is made about the importance of being able to use learning strategies from the point of view of formation future foreign language teacher’s professional competence.